Inflorescence shoot elongation, but not flower primordia formation, is photoperiodically regulated in Arabidopsis lyrata - Kemi, Ulla (Ann Bot, 2019)
BACKGROUND AND AIMS: Photoperiod contains information about the progress of seasons. Plants use the changing photoperiod as a cue for the correct timing of important life history events, including flowering. Here the effect of photoperiod on flowering in four Arabidopsis lyrata populations originating from different latitudes was studied, as well as expression levels of candidate genes for governing the between-population differences. METHODS: Flowering of plants from four A. lyrata populations was studied in three different photoperiods after vernalization. Flowering development was separated into three steps: flower primordia formation, inflorescence shoot elongation and opening of the first flower. Circadian expression rhythms of the A. lyrata homologues of GIGANTEA (GI), FLAVIN-BINDING, KELCH REPEAT, F-BOX 1 (FKF1), CONSTANS (CO) and FLOWERING LOCUS T (FT) were studied in three of the populations in the intermediate (14 h) photoperiod treatment. KEY RESULTS: Most plants in all populations formed visible flower primordia during vernalization. Further inflorescence development after vernalization was strongly inhibited by short days in the northern European population (latitude 61°N), only slightly in the central European population (49°N) and not at all in the North American populations (36°N and 42°N). In the 14 h daylength, where all plants from the three southernmost populations but only 60 % of the northernmost population flowered, the circadian expression rhythm of the A. lyrata FT was only detected in the southern populations, suggesting differentiation in the critical daylength for activation of the long-day pathway. However, circadian expression rhythms of A. lyrata GI, FKF1 and CO were similar between populations. CONCLUSIONS: The results indicate that in A. lyrata, transition to flowering can occur through pathways independent of long days, but elongation of inflorescences is photoperiodically regulated.